2018
DOI: 10.7326/m17-3074
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Prescription Drug Monitoring Programs and Nonfatal and Fatal Drug Overdoses

Abstract: Background Prescription drug monitoring programs (PDMPs) are a key component of the president's Prescription Drug Abuse Prevention Plan to prevent opioid overdoses in the United States. Purpose To examine whether PDMP implementation is associated with changes in nonfatal and fatal overdoses; identify features of programs differentially associated with those outcomes; and investigate any potential unintended consequences of the programs. Data Sources Eligible publications from MEDLINE, Current Contents Conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(158 citation statements)
references
References 33 publications
5
153
0
Order By: Relevance
“…PDMPs differ greatly between states, and legal mandates for PDMP use by prescribers and pharmacists have been limited until recently. Furthermore, there is a current lack of PDMP integration into EMRs and pharmacy operating systems which limits their accessibility and subsequent use . Pharmacists should realize that electronic resources like PDMPs are one of several tools to be used together to evaluate opioid misuse risk and to maintain patient engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDMPs differ greatly between states, and legal mandates for PDMP use by prescribers and pharmacists have been limited until recently. Furthermore, there is a current lack of PDMP integration into EMRs and pharmacy operating systems which limits their accessibility and subsequent use . Pharmacists should realize that electronic resources like PDMPs are one of several tools to be used together to evaluate opioid misuse risk and to maintain patient engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists should realize that electronic resources like PDMPs are one of several tools to be used together to evaluate opioid misuse risk and to maintain patient engagement. Some PDMPs and supply‐side policies may potentially end up unintentionally harming patients if not combined with expansion of treatment and harm reduction interventions like naloxone …”
Section: Discussionmentioning
confidence: 99%
“…We examined references from the selected materials to identify additional articles that met the inclusion criteria. To ensure that we captured all relevant studies, we compared our yielded articles with the evaluations included in the following review papers: Haegerich et al., 2014; Beaudoin et al., 2016; Finley et al., 2017; and Fink et al., 2018 . We conducted the search in summer 2018 and no additional articles were added after September 1, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies aggregated evidence from specific interventions and integrated strategies in a single review . Reviews published in the past two years of prescription drug monitoring program (PDMP) evaluations are inconclusive with regard to PDMP effects on overdose and other outcomes . Reviews that synthesize evaluations of multiple interventions published prior to 2016 identified some promising state policies to decrease opioid prescribing, including PDMPs, policies targeting insurance practices, pain clinic regulations, clinical guidelines, and naloxone access laws .…”
Section: State Policies To Curb Opioid Misusementioning
confidence: 99%
“…How PDMPs are structured and operated (e.g., functionality, funding, oversight and evaluation, data sharing, and prescriber and dispenser requirements) varies among states and across time. Such heterogeneity may modify PDMP effectiveness but has often been overlooked in prior studies …”
Section: Introductionmentioning
confidence: 99%